2001
DOI: 10.1007/s004250000399
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of heavy metals in epidermal glands of the waterlily (Nymphaeaceae)

Abstract: This study investigates the anatomical aspects of heavy-metal accumulation in the waterlily (Nymphaea 'Aurora', Nymphaeaceae). Epidermal glands were identified by light microscopy on the abaxial side of the leaf laminae and on the epidermis of the rhizome; glandular trichomes were observed in the petiole epidermis. Glands were not observed in the roots. Accumulation of heavy metals in these glands was monitored using a scanning electron microscope equipped for energy-dispersive spectroscopy. Further experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 15 publications
3
44
0
5
Order By: Relevance
“…Accumulation in nonglandular trichomes of several hyperaccumulating plants, including Arabidopsis halleri (Küpper et al 2000;Sarret et al 2000;Zhao et al 2000), Alyssum sp. (Broadhurst et al 2004), and non-hyperaccumulating plants, including Brassica juncea (Salt et al 1995), Arabidopsis thaliana (Ager et al 2003;Domínguez-Solís et al 2004), pumpkin (Cucurbita moschata, Iwasaki and Matsumura 1999), and waterlily (Nymphaea sp., Lavid et al 2001), has been reported. However, the mechanism of metal accumulation and excretion of metals in these structures and their exudates are still under investigation.…”
mentioning
confidence: 98%
“…Accumulation in nonglandular trichomes of several hyperaccumulating plants, including Arabidopsis halleri (Küpper et al 2000;Sarret et al 2000;Zhao et al 2000), Alyssum sp. (Broadhurst et al 2004), and non-hyperaccumulating plants, including Brassica juncea (Salt et al 1995), Arabidopsis thaliana (Ager et al 2003;Domínguez-Solís et al 2004), pumpkin (Cucurbita moschata, Iwasaki and Matsumura 1999), and waterlily (Nymphaea sp., Lavid et al 2001), has been reported. However, the mechanism of metal accumulation and excretion of metals in these structures and their exudates are still under investigation.…”
mentioning
confidence: 98%
“…A função dos tricomas glandulares na tolerância a metais pesados é amplamente discutida na literatura, sendo descritos como células epidérmicas que podem acumular metais pesados ou secretá-los, visto que estas estruturas fazem parte do tecido mais externo da folha (Salt et al 1995;MacFarlane & Burchett 1999;Küpper et al 2000;Psaras et al 2000;Lavid et al 2001a).…”
Section: Discussionunclassified
“…Em condições de deficiência de Ca pode haver a reabsorção dos cristais, indicando que há uma estocagem temporária de Ca no idioblasto (Franceschi & Horner 1980). O Cd, juntamente com o Ca, pode se acumular no vacúolo formando cristais, como observado por Lavid et al (2001a) em Nymphaea. Da mesma forma, Mazen & El Maghraby (1997) verificaram que durante a exposição de Eichhornia crassipes (Mart) Solms aos metais Cd, Pb, Sr ocorreu o aumento progressivo da formação de cristais de oxalato de cálcio (ráfides).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…(Espinoza-Quinones et al, 2005), Potamogeton crispus (Aysel et al, 2010), Potamogeton pectinatus and Potamogeton malaianus (Peng et al, 2008), Typha angustifolia (Dilek and Ahmet, 2004), Myriophyllum heterophyllum (Aysel et al, 2010), Lemna minor (Yeşim et al, 2003) and Azolla caroliniana (Bennicelli et al, 2004). In addition, Lavid et al (2000) discovered that water lilies (Nymphaea variety) are endowed with anatomical and physiological traits that allow them to thrive on water with high concentrations of heavy metals such as Cd, Hg, Ni and Co.…”
Section: Introductionmentioning
confidence: 99%